Conhecimento e utilização de mamíferos por duas comunidades em uma Área de Proteção Ambiental (APA/Araripe) : uma abordagem etnomastozoológica - MELO, Robson Soares de (2013)
Studies on the knowledge and use of natural resources are a crucial tool to identify the way each individual observe and use the environment they live. Each person has a proper knowledge of the environment, and this knowledge can vary by gender, age, housing conditions and schooling. In this context, this study aims to verify and list the species of mammals used in two communities located in the Araripe Area of Environmental Protection – APA/Araripe, verify possible significant difference in knowledge regarding the use of mammals according to sex and age group, identify the diseases treated with zootherapics and obtain information about mammalian parts use as medicine and about medicine preparation. The study was conducted in two communities located in the APA/Araripe: Sítio Betânia community and Caldas community, both belonging to the city of Barbalha (Ceará, Brazil). The data collection was performed through semi-structured forms, where the interviewed were randomly selected through stratified random sampling, so that all individuals in the community had the same chance of being selected. For this stratification we considered sex and three age groups based on the classification criteria of the Ministry of Health: adolescents (12-19 years), adults (20-59 years) and elderly (above 60 years). A total of 229 interviews were conducted between October and November of 2012. We verify that men know and use more the mammals as zootherapics and as food resource than women, while for the religious mystic use there were no significant differences between genders. In relation to age, it was observed that adults know and use more mammals as zootherapics and the elderly use more as food resource. This study reveals that the practice of using mammals still persist even in communities inserted in conservation units where laws are stricter. Probably, traditions, poverty and the lack of more rigorous inspections lead to such conducts. Thus, the development of a rigorous management plan considering social and cultural aspects of the local communities is highly recommended.